The Social Perception of Heroes and Murderers: Effects of Gender-Inclusive Language in Media Reports - Hansen, Karolina; Littwitz, Cindy; Sczesny, Sabine (Frontiers in Psychology, 2016)
The way media depict women and men can reinforce or diminish gender stereotyping. Which part does language play in this context? Are roles perceived as more gender-balanced when feminine role nouns are used in addition to masculine ones? Research on gender-inclusive language shows that the use of feminine-masculine word pairs tends to increase the visibility of women in various social roles. For example, when speakers of German were asked to name their favorite “heroine or hero in a novel”, they listed more female characters than when asked to name their favorite “hero in a novel”. The research reported in this paper examines how the use of gender-inclusive language in news reports affects readers’ own usage of such forms as well as their mental representation of women and men in the respective roles. In the main experiment, German participants (N = 256) read short reports about heroes or murderers which contained either masculine generics or gender-inclusive forms (feminine-masculine word pairs). Gender-inclusive forms enhanced participants’ own usage of gender-inclusive language and this resulted in more gender-balanced mental representations of these roles. Reading about “heroines and heroes” made participants assume a higher percentage of women among persons performing heroic acts than reading about “heroes” only, but there was no such effect for murderers. A post-test suggested that this might be due to a higher accessibility of female exemplars in the category heroes than in the category murderers. Importantly, the influence of gender-inclusive language on the perceived percentage of women in a role was mediated by speakers’ own usage of inclusive forms. This suggests that people who encounter gender-inclusive forms and are given an opportunity to use them, use them more themselves and in turn have more gender-balanced mental representations of social roles.